SINTESIS DAN KARAKTERISASI WOLLASTONIT BERBAHAN DASAR ALAMI DENGAN METODE HIDROTERMAL - Rianda -; Zulhadjri -; Syukri Arief (Jurnal Riset Kimia, 2015)
Indonesia is one of huge paddy producing countries so that it also produces rice husk in a great number. Rice husks contain high silica. Which is good in silica compounds synthesis such as Wollastonit (CaSiO3). Nowadays Wollastonit has attracted great intension doe to its ability to increase mechanical properties of a material. In this work, rice husk was taken from Sariak Laweh, Lima Puluh Kota district and CaO was taken from Halaban, in the same district. Analysis with XRF show that SiO2 and CaO content of both samples were high enough, 97% and 98% which indicated their good potential as silica and calcium source in to synthesize of Wollastonit. Characterization XRD and SEM were found that the Wollastonit obtained which rice husks gave good result.